Hartnup disease-causing SLC6A19 mutations lead to B0AT1 aberrant trafficking and ACE2 mis-localisation implicating the endoplasmic reticulum protein quality control - Alkhofash, Nesreen F.; Ali, Bassam R. (Frontiers in Cell and Developmental Biology, 2025)
IntroductionThe interaction between angiotensin-converting enzyme 2 (ACE2) and the sodium-dependent Broad neutral Amino acid Transporter 1 (B0AT1), encoded by the SLC6A19 gene, is increasingly recognized as pivotal in both physiological and pathological contexts. B0AT1 facilitates neutral amino acid transport and nutrient absorption, while ACE2 regulates vascular homeostasis and inflammation through the renin-angiotensin system. Mutations in SLC6A19 are implicated in Hartnup disease, a metabolic disorder characterized by defective amino acid transport. However, the cellular mechanisms underlying Hartnup disease-causing mutations' impact on B0AT1 and ACE2 function remain unclear.MethodsThis study evaluated the subcellular localization and trafficking of 18 Hartnup disease-causing B0AT1 variants using experimental approaches including biochemical assays and In Silico analysis. The impact of these variants on ACE2 trafficking and plasma membrane targeting was also assessed to elucidate their interplay.ResultsNine B0AT1 variants (R57C, G93R, R95P, R178Q, L242P, G284R, S303L, D517G, P579L) were found to be retained in the endoplasmic reticulum, impairing their trafficking to the plasma membrane. These variants were distributed across multiple B0AT1 structural domains. Importantly, several of these ER-retained variants, particularly R178Q and S303L, significantly disrupted ACE2 intracellular trafficking and its localization to the plasma membrane, indicating a direct effect on ACE2 subcellular targeting.DiscussionThe findings reveal that Hartnup disease-causing mutations can lead to ER retention of B0AT1, which in turn has a variable effect on ACE2 trafficking. This disruption likely contributes to Hartnup disease pathogenesis by impairing amino acid transport and may influence ACE2-mediated physiological functions beyond the renin-angiotensin system. Understanding these molecular mechanisms enhances insight into ACE2-B0AT1 interactions and could inform future therapeutic strategies and biomarker development for related disorders. Further research is needed to explore these pathways and their implications in disease.